Increasing adolescent firearm homicides and racial disparities following Florida's 'Stand Your Ground' self-defence law. Issue 2 (20th December 2019) - Degli Esposti, Michelle; Wiebe, Douglas J; Gravel, Jason; Humphreys, David K
Abstract : Establishing whether specific laws impact rates of firearm homicide in adolescents is critical for identifying opportunities to reduce preventable adolescent death. We evaluated Florida's Stand Your Ground law, enacted October 2005, using an interrupted time series design from 1999 to 2017. We used segmented quasi-Poisson regression to model underlying trends in quarterly rates of adolescent (15–19 years) firearm homicide in Florida and disaggregated by race (Black/White). We used synthetic and negative controls (firearm suicide) to address time-varying confounding. Before Florida's Stand Your Ground law, the mean quarterly rate was 1.53 firearm homicides per 100 000 adolescents. Black adolescents comprised 63.5% of all adolescent firearm homicides before and 71.8% after the law. After adjusting for trends, the law was associated with a 44.6% increase in adolescent firearm homicide. Our analysis indicates that Florida's Stand Your Ground is associated with a significant increase in firearm homicide and may also exacerbate racial disparities.